Orthoptic Services in the UK and Ireland During the COVID-19 Pandemic. Issue 1 (5th June 2020) - Rowe, Fiona; Hepworth, Lauren; Howard, Claire; Lane, Steven
Aim: COVID-19 has widely impacted hospital services. The purpose of this study was to determine the impact of COVID-19 on Orthoptists and their clinical practice in the UK, Ireland, and Channel Islands. Methods: We conducted a prospective survey-based cross-sectional study using an online survey aiming for coverage of orthoptic departments across the UK, Ireland, and Channel Islands. We circulated the online survey through the British and Irish Orthoptic Society that reaches over 95% of UK and Irish orthoptic services, and through social media and orthoptic research networks. Results: The survey response rate was 79%. The survey was completed by orthoptic departments, on average 10 days post lockdown. Many orthoptic services were cancelled/paused with remaining services largely reserved for emergency cases and urgent care. A substantial rise in tele-consultations was reported by 94%, which largely consisted of telephone and video calls and which was regarded generally as working well. Barriers to tele-consultations were mainly IT related but with concerns also raised regarding ethical and confidentiality issues. Shortage of personal protective equipment (PPE) was reported by one third of departments along with issues relating to conflicting information about the use of PPE. Conclusions: We have reported information on the changing face of orthoptic clinical practice during the COVID-19 pandemic. The survey has highlighted emerging tele-consultation practice and the importance of centralised profession-specific guidelines.